2018
DOI: 10.1371/journal.pone.0203609
|View full text |Cite
|
Sign up to set email alerts
|

Home birth and its determinants among antenatal care-booked women in public hospitals in Wolayta Zone, southern Ethiopia

Abstract: IntroductionAntenatal care (ANC), health facility birth and postnatal care services are proved to reduce maternal and newborn morbidity and mortality. In Ethiopia, even though antenatal care coverage is good, still home birth is high. This study aimed to assess the prevalence and determinants of home birth among women who were booked for ANC in public hospitals in Wolaita zone, southern Ethiopia.MethodsA cohort study was conducted from February to May 2017 among 554 third trimester pregnant mothers who visited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 26 publications
6
17
2
1
Order By: Relevance
“…Consistent with previous studies [23,28,39,40] our nding suggests that women who exposed to media were 20% lower chances of home delivery in compared with women without media exposure. Media promotion of institutional delivery and danger of home delivery may in uence mothers to develop positive behavior towards delivering in a health facility.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies [23,28,39,40] our nding suggests that women who exposed to media were 20% lower chances of home delivery in compared with women without media exposure. Media promotion of institutional delivery and danger of home delivery may in uence mothers to develop positive behavior towards delivering in a health facility.…”
Section: Discussionsupporting
confidence: 91%
“…The provinces with the highest proportion of the population in poverty have the highest frequency of home birth. In other settings, it has been reported that home deliveries are a consequence of lack of access to health services, that is, it is not by choice [45, 46]. Home birth represents one of the greatest challenges to the goal of reducing maternal mortality in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…A published review stated that higher socioeconomic status, education, privileged ethnicities, Hindu people, having access to transport and health services, getting family support, able to decide themselves, empowered, and having a birth preparedness plan are the major determinants of maternal health [26]. Another study concluded that emphasis should be given to women without education, to improve accessibility and provide advice on birth preparedness and danger signs to reduce home delivery [32].…”
Section: Characteristicsmentioning
confidence: 99%